Study On Implementation Of Watergate Control System From Manual To Automatic Based Arduino Nano ATmega328 - Syafrudin, Ahmad; Jeckson, Jeckson; Afrida, Yenni (Universitas Muhammadiyah Yogyakarta, 2024)
The system for processing river water into clean water by operating sluice gates which are controlled manually by operators often causes problems (human error), so a system must be created that is capable of controlling sluice gates automatically. The turbidity sensor detects water turbidity which is then accepted by the Arduino nano as the basis for controlling the water gate. In this research, data collection techniques were carried out using interviews with resource persons (operators), observation and literature study. After the automatic sluice control system based on the Arduino nano ATmega328 was implemented, the results obtained were: When the water conditions are muddy and murky, relay one is